Unveiling the Adoption of Contemporary Lifestyles - Asiah, Siti Nur; Liky Faizal; Nurnazli (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
As a student, ideally prioritize consumptive behavior that prioritizes academic affairs. In fact, students often focus on lifestyle dimensions and aspects outside academia. This raises questions about students' motivations and the extent of their awareness of basic needs. This study examines the consumption patterns of State Islamic University (UIN) Raden Intan Lampung students who adhere to a modern lifestyle. This study explores the impact of Sharia economic law on the consumption behavior of the class of 2020 student groups who took the Sharia Economic Law program at the Sharia Faculty. This research includes field research with a quantitative approach. The methodology used is a descriptive analysis study. The primary data of this study consisted of Sharia Economic Law students class of 2020 from the Sharia Faculty of UIN Raden Intan Lampung. Data collection was carried out through interviews, observations, and questionnaires. The results of the study found that. Students majoring in Sharia Economic Law at UIN Raden Intan Lampung do not follow the Islamic Economic Law, especially the theory of Al Ghazali Consumption. Their emphasis on complementary and aesthetic needs, rather than basic needs, shows a lack of awareness of basic needs and a tendency towards extravagance and luxury.